2013
DOI: 10.3354/ab00490
|View full text |Cite
|
Sign up to set email alerts
|

Population subdivision of saddled seabream Oblada melanura in the Aegean Sea revealed by genetic and morphometric analyses

Abstract: The population structure of marine fishes is often cryptic, due to limited knowledge about life history and ecological habitats. Understanding environmental stability is a challenge to retrieve possible structuring patterns responsible for dispersal and demographic habits. In the present study, a combination of genetic and phenotypic assessments was applied in order to investigate population structure of the saddled seabream Oblada melanura in the Aegean Sea, eastern Mediterranean basin. Analyses of 6 microsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 70 publications
1
11
0
Order By: Relevance
“…Similar results were recorded, for the same species, using a different set of microsatellite primers (Gkafas et al, 2013), and in other sparid fish in the Mediterranean Sea (Franchini et al, 2011). High genetic diversity is fundamental for maintaining the adaptability of natural fish populations and sustainable yields in fisheries (Kenchington et al, 2003).…”
Section: Discussionsupporting
confidence: 69%
“…Similar results were recorded, for the same species, using a different set of microsatellite primers (Gkafas et al, 2013), and in other sparid fish in the Mediterranean Sea (Franchini et al, 2011). High genetic diversity is fundamental for maintaining the adaptability of natural fish populations and sustainable yields in fisheries (Kenchington et al, 2003).…”
Section: Discussionsupporting
confidence: 69%
“…Güven (2011) reported that abyssal gradients have also an effect on gene flow of Sepia officinalis in the North-West Levantine region. There are subdivisions found between saddled seabream Oblada melanura populations in North Aegean Sea which might be the reason of a deep trench of 1500 m, presenting a physical geographical boundary in the Central Aegean (Gkafas et al, 2013). In the present study, the samples from LSK population were collected from a lagoon which has a more than 4000 meters deep trench (Rhodes Abyssal Plain) just starting from the shore.…”
Section: Discussionmentioning
confidence: 90%
“…Ocean circulation acts as a barrier to the dispersal of larvae and leads to genetic structuring (Karlsson et al, 2009;Castillo-Olguín et al, 2012;Prieto-Ríos et al, 2014) and morphological differentiation (AnvariFar et al, 2013;Gkafas et al, 2013). The morphological variability recorded among different localities or geographic variants may be due to the genetic structure or to differences in the environmental conditions that prevail in each geographic area.…”
Section: Discussionmentioning
confidence: 99%